100th Anniversary of Svalbard Treaty: Disputes and Challenges, Opportunities for Turkey - Onur Limon (International Journal of Politic and Security, 2021)
The sovereignty of a state over a territory is generally accepted as the basic principle of modern international law. This state of sovereignty may be limited by treaties or the exercise of sovereignty may be subject to a specific condition. The Svalbard Treaty, signed in 1920, defines Norway’s full and absolute sovereignty over the Svalbard Archipelago, and limits this sovereignty on the obligation to treat the states that are parties to the Treaty equally in certain areas specified in the Treaty. This restriction provides the states that are party to the Svalbard Treaty the right to request equal treatment from Norway on behalf of their citizens and companies in the Svalbard Archipelago. Especially the developments in the field of international maritime law since 1920 have brought along discussions on the geographical scope of the implementation of the Svalbard Treaty. The issue that is the basis for dispute in the Svalbard Treaty; It is not about whether the non-discriminatory right of economic access has reached Norwegian sovereignty beyond the territorial waters of the Svalbard Archipelago, but whether this sovereignty is restricted according to the Svalbard Treaty. The aim of this article is to examine why, in its 100th year, the Svalbard Treaty has failed to resolve disputes between states parties to the Treaty and why Turkey is not a party to the Treaty of Svalbard and why it should be a party.